Occupational Health Problems Among Female Sewing Machine Operators - Neha Gahlot , Manju Mehta and Kiran Singh, (Indian Journal of Extension Education, 2017)
A vast majority of women working in textile and apparel industries serve as sewing machine operators. Sitting in a fixedposition constantly in view of the sight requirements at the machine, leads to a static burden that threatens the health of theworker. The present study was formulated to explore the work profile of female sewing machine operators and theirresultant health problems. The present study was conducted with 80 female sewing machine operators who wereperforming sewing activity from last 4 years in Hisar city of Haryana state. A pre tested and well planned questionnairewas used to along with interview schedule to collect the responses of the respondents. The results of the study revealed thatthe mean working years of the respondents were 11.91 where the mean working hours were 5.74. About 91.25 per centrespondents did not have rest during the work. Among the physiological problem, lower back pain (72.50%) and bodyache (52.50%), in symptomatic problems, muscle stiffness (50%), and joint stiffness (45%) and in psychologicalproblems, low motivation (33.75%) and frequent bad mood (16.25%) were found to be the most due to sewing activity. Asignificant difference was found between health problems and working years, working hours and age of the respondents.